Theory and practice of valuation approaches in renewable energy investments: a survey among investment professionals. (6th November 2019) - Hürlimann, Christian; Al-Ali, Jasim; Bengoa, Dolores S.
This paper reports the results of a survey among Swiss and German investors in renewable energy (RE) - a challenging undertaking due to the restricted data access for those typically non-trade assets. The research's focus is placed on capital budgeting techniques, risk assessment, risk mitigation, cost of capital approaches, and risk-adjustment processes. The results are both reassuring and surprising. The majority of organisations still employ well-established discounted cash flow based techniques while other approaches propagated in finance theory, such as the certainty equivalent method, are seldom applied. A surprising number of organisations still use their firm's risk within discount rates in RE valuations instead of project risk. Beside of taking systematic risk into account in line with the capital asset pricing model, various diversifiable unsystematic risk components are considered in RE valuation. We also find clear evidence about materialised risk influencing personal risk preferences and some evidence about cultural differences in valuation.